THE INFLUENCE OF BRAND AND TRUST ON ONLINE CONSUMER BUYING INTEREST - Dede Suleman; Yohanes Totok Suyoto; Wiwin Wianti; Etik Dwi Styaningrum; Supriatin; Rohani Lestari Napitupulu; Helmy Ivan Taruna (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This research study aims to investigate the impact of brand and trust on the online consumer buying interest. With the increasing number of online shopping platforms, it is essential to understand the factors that drive consumers' purchasing decisions. The study will be conducted using a quantitative research approach, and data will be collected through a survey. The sample will consist of online shoppers who have made purchases in the last six months. The study will explore the relationship between brand and trust and their effect on online consumer buying interest. The study will also investigate the mediating effect of trust on the relationship between brand and online consumer buying interest. The study will use a regression analysis to analyze the data. The findings of this research will have implications for marketers and businesses looking to improve their online sales. The study will provide insight into the importance of building a strong brand and fostering consumer trust in driving online purchasing decisions. This research will contribute to the existing literature on online consumer behavior and provide a better understanding of the factors that influence online buying interest.